Structural basis of vitamin C recognition and transport by mammalian SVCT1 transporter - Mingxing Wang; Jin He; Shanshan Li; Qianwen Cai; Kaiming Zhang; Ji She (Nature Communications, 2023)
Sodium-dependent vitamin C transporters are responsible for vitamin C uptake and tissue distribution in mammals. Here, authors present cryo-EM structures of mouse SVCT1 in both the apo and substrate-bound states, revealing the structural basis of substrate recognition and transport.